PENGARUH EDUKASI MENGGUNAKAN MEDIA BUKLET BERBAHASA DAERAH TERHADAP PERAN ORANGTUA DALAM PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK (Studi pada siswa kelas V di Madrasah Ibtidayah Negeri Sekadau) - Nurazis, Dayang AK; Mardjan, Mardjan; Ridha, Abduh (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Oral health problems in children occur due to the lack of parental knowledge on the importance of oral health care.This study aimed to find out the the influence of local language booklet as educational media towards parents’ role in maintaining children’s oral health (grade v students of Madrasah Ibtidaiyah Negeri Sekadau)A quasi experimental design, as well as a pre testpost test non equivalent control group approach, was carried out in this study. The samples were 80 samples. 40 out of them were given oral health education using local language booklet. While the rest were not given any treatment. The parametric statistics used were paired and unpaired t test. The data then analyzed by using univariate and bivariate analysis.The study revealed that there were differences of parental knowledge in booklet group (p value=0,000) and an increase of students’ OHI-S (p value=0,000) before and after the treatment. Also, there were differences of parental knowledge (p value=0,006) and students’ OHI-S (p value=0,000) between treatment and control groups.Based on the findings, health department, public health centers, and schools should increase the parents’ knowledge about oral health by providing booklet, posters, and leaflet. By using local language, local people can easily understand the information as local language is used as daily conversation. Besides, they can implement the information they get to their children.Key words: booklet, educational booklet on oral health